2023
DOI: 10.1111/apt.17790
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial: predictive factors for response to gut‐directed hypnotherapy for refractory irritable bowel syndrome, a post hoc analysis

Jade Devenney,
Syed S. Hasan,
Julie Morris
et al.

Abstract: SummaryBackgroundGut‐directed hypnotherapy is effective for patients with irritable bowel syndrome (IBS). Despite its considerable evidence base, gut‐directed hypnotherapy is not widely available and remains a limited resource. This emphasises the need to select patients who are most likely to benefit.AimTo determine whether baseline patient characteristics were predictive of response to gut‐directed hypnotherapy in patients with IBSMethodsWe conducted a secondary analysis of outcomes of 448 patients with refr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
4
6
0
Order By: Relevance
“…However, those with a higher PSS, which measures the degree to which situations in one's life are appraised as stressful, were less likely to respond to the app and trended towards non‐completion of the program (though the latter did not reach significance). This is similar to a result seen in a recently conducted clinical trial looking at predictive factors for response to gut‐directed hypnotherapy for refractory IBS, which showed that those who achieved ≥30% improvement in abdominal pain scores had a significantly higher baseline IBS‐SSS and lower baseline hospital anxiety and depression score 20 …”
Section: Discussionsupporting
confidence: 86%
“…However, those with a higher PSS, which measures the degree to which situations in one's life are appraised as stressful, were less likely to respond to the app and trended towards non‐completion of the program (though the latter did not reach significance). This is similar to a result seen in a recently conducted clinical trial looking at predictive factors for response to gut‐directed hypnotherapy for refractory IBS, which showed that those who achieved ≥30% improvement in abdominal pain scores had a significantly higher baseline IBS‐SSS and lower baseline hospital anxiety and depression score 20 …”
Section: Discussionsupporting
confidence: 86%
“… 3 Indeed, recent research suggests that patients with higher baseline depression are less likely to experience improvements in pain with GDH, and patients with greater anxiety and/or lower quality of life at baseline are more likely to drop out. 13 Given the high rates of both discrimination and mental health concerns in individuals who identify as transgender or gender diverse, it is likely that for these patients, shared decision making is particularly important. 14 It is possible that patients who self-identify as transgender or gender diverse and who are actively experiencing gender dysphoria may have better outcomes with individual therapy, including engaging in other evidence-based brain-gut behavior therapies or working first with a therapist who specializes in gender-related concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Network meta-analysis indicate that self-administered or minimal-contact CBT, face-to-face CBT, and gut-directed hypnotherapy have the best evidence of efficacy, 41 improving outcomes in up to three-quarters of sufferers. 42 Treatments can be effectively delivered individually or in a group setting. 43 More formal involvement of a psychiatrist in the multidisciplinary team may also be warranted.…”
Section: Role Of Mental Health Cliniciansmentioning
confidence: 99%
“…Through evidence‐based interventions such as cognitive behavioral therapy (CBT), the psychologist can help patients to modulate their pain experience, challenge their illness perceptions, manage stress, and cope with anxiety and fear associated with symptoms, all of which can in turn modulate central sensitization. Network meta‐analysis indicate that self‐administered or minimal‐contact CBT, face‐to‐face CBT, and gut‐directed hypnotherapy have the best evidence of efficacy, 41 improving outcomes in up to three‐quarters of sufferers 42 . Treatments can be effectively delivered individually or in a group setting 43 …”
Section: Role Of Mental Health Cliniciansmentioning
confidence: 99%